Dynamic alternate buffer switching and congestion control in wireless multimedia sensor networks - Sumathi, K.; Pandiaraja, P. (Peer-to-peer networking and applications, 2020)
Normally sensor nodes are located at unattended environment which has low battery power. The wireless hypermedia sensor based networks have huge capacity and continuous flow of data from source to sink. Congestion arises at the time of incoming data is greater than available resources. The congestion causes packet loss, buffer over flow, energy wastage and increases end to end delay. The proposed method Dynamic Alternate Buffer switching and Congestion Control is used to manage congestion in an efficient manner. In which congestion is detected based on remaining buffer, remaining energy and trust level of the sensor nodes. T his approach is based on cost evaluation method which decides primary and spare buffers at run time. This method is used to enable dynamic buffer switching and optimize the effect of congestion. The performance of BETCC compared with various existing protocol like TCEER and TFCC in terms of energy consumption and data loss ratio.